Pengembangan Lembar Kerja Peserta Didik (LKPD) IPA Berbasis Discovery Learning - Wulan Maulita; Tias Ernawati; Astuti Wijayanti (Universitas Sarjanawiyata Tamansiswa, 2020)
This research was aimed to 1) develop a Science Learning LKPD based on Discovery Learning on subject materials Work and Simple Machine in Daily Life for VIII Middle School Students; 2) find out the feasibility of Discovery Learning based LKPD on subject materials Work and Simple Machine in daily life for VIII grade junior high school students; and 3) knowing students responses to the development of Discovery Learning-based LKPD on subject materials Work and Simple Machine in daily life for VIII grade junior high school students. This research includes development research (design research) with a 4-D development model. Data collection techniques used assessment instruments by material experts, media experts, peer reviewers, science teachers, and grade VIII students in junior high schools. The data analysis technique uses the quality analysis of LKPD. Based on the assessment of expert lecturers, peer reviewers, and science teachers, the average score of 4.31 was obtained with a percentage of 86.43% stating that the quality of the LKPD was very good (VG). The results of students' responses obtained an average score of 4.31 with a percentage score of 86.43% stating that the quality of the LKPD IPA Very Good (VG). It can be concluded that the developed Natural Sciences LKPD is suitable for use in learning science in schools.